2022
DOI: 10.22361/jfmer/151646
|View full text |Cite
|
Sign up to set email alerts
|

A Delphi Technique Analysis of Drivers of Outsourcing Decisions Among Multi-Tenanted Shopping Mall Owners in Ghana

Abstract: The purpose of this study was to assess the drivers of outsourcing decisions of multi-tenanted shopping mall owners for facilities management in Ghana. The study was conducted using nine owners of multi-tenanted shopping malls in Ghana with a history and experience in outsourcing retail properties to third party facility management firms (n = 9) and facilities managers who are experts in providing outsourced services (n = 5). Using the Delphi technique, five surveys were conducted (Delphi polls)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…FM services can be provided using an in-house sourcing approach (Barret and Baldry, 2003;Ikediashi, 2014;Atkin and Brooks, 2015;Tannor et al, 2022) or outsourcing (Ahamed et al, 2013;Toe, 2015;Amos and Gadzekpo, 2016;Abisuga et al, 2020). These two sourcing approaches are well known approaches in the provision of FM services.…”
Section: Facilities Management Sourcing Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…FM services can be provided using an in-house sourcing approach (Barret and Baldry, 2003;Ikediashi, 2014;Atkin and Brooks, 2015;Tannor et al, 2022) or outsourcing (Ahamed et al, 2013;Toe, 2015;Amos and Gadzekpo, 2016;Abisuga et al, 2020). These two sourcing approaches are well known approaches in the provision of FM services.…”
Section: Facilities Management Sourcing Approachesmentioning
confidence: 99%
“…Other studies have also identified hidden costs associated with making an outsourcing decision, losing control over outsourced activities, failing to plan an exit strategy, ambiguous terms and conditions, possible contract breach and lack of cohesiveness amongst team members as some of the disadvantages associated with outsourcing of FM services (Dekkers, 2011;Driedonks et al, 2014;Okoro et al, 2020). Tannor et al (2022) also found that 88% of multi-tenanted office building owners in Ghana prefer to manage their buildings in-house due to their strategic advantages. The study showed that an in-house sourcing strategy allows for innovation on the part of the inhouse FM team, and prevents redundancies that can develop from overdependence on external service providers.…”
Section: 22mentioning
confidence: 99%
See 3 more Smart Citations